Flexural Behavior of Lightweight Ferrocement Sandwich Composite Beams - El-Wafa, Mahmoud Abo; Fukuzawa, Kimio (University of Science and Technology, Sana'a, 2010)
The structural behavior of lightweight ferrocement (LWF) sandwich composite beams is investigated by conducting flexural tests on eight simply supported rectangular beams under three point loads. The main objective of the study is to investigate the comprehensive comparisons of eight beams represented in six lightweight ferrocement (LWF) beams and two reinforced concrete (RC) beams. The performance of the LWF and RC beams is investigated in terms of crack load, load-deflection curves, stiffness, energy absorption capacity, ductility index, ultimate flexural load-to-weight ratio, load-strain curves, crack patterns, number of cracks, average crack width, crack spacing and the failure mode. The method outlined by ACI Building Code is used to compute ultimate moment capacities. The test results reveal the remarkable enhancement in the flexural behaviour and potential application of lightweight ferrocement (LWF) sandwich composite beams to produce lightweight structural elements as compared to that of the reinforced concrete (RC) beams, which leads towards the industrialization of building system and meets with innovation and responsible application of concrete construction technology results in better efficiency of the composite.